Peningkatan Kapasitas dan Mutu Produk Brownies Tempe di Industri Rumah Tangga (IRT) “Browniesta” melalui Introduksi Teknologi Tepat Guna - Dwi Ishartani; Windi Atmaka; Lia Umi Khasanah; Setyaningrum Ariviani; Siswanti Siswanti (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2021)
Tempeh had been recognized worldwide as a superfood. In Pengkok Village, Kedawung Sub-district, Sragen Regency, there were several traditional tempeh producers which supply fresh tempeh around Kedawung Sub-district. Tempeh produced in this area was also used as raw material for brownies production. "BROWNIESTA" is a Small Medium Enterprise (SME) which produces brownies made from tempeh. The demand of tempeh brownies was high, but it was difficult for SME "BROWNIESTA" to fulfill the demand due to the lack number of ovens. In addition, packaging, labels and the quality of the products had been unstable due to limited understanding of Good Manufacturing Practices (GMP) concept in food production. This community service introduced appropriate technology for SME "BROWNIESTA" in the form of: 1) introduction of gas-fired ovens, 2) introduction of packaging and labels and 3) GMP training according to BPOM guidelines. Partners actively participated in providing materials for the introduced oven trials, providing materials and tools for evaluation of product sensory quality improvement and facilitating the implementation of GMP training. Based on the evaluation results, the sensory quality of brownies produced using the introduced oven had increased as indicated by its softer texture and smoother crust that is not caramelized. The product was also packaged properly with product information on the label attached to the packaging. Oven introduction also increased the production capacity up to 150%. SME “BROWNIESTA” implemented better food production practices after completing GMP training. Therefore, it could be concluded that the introduction of appropriate technology in SME "BROWNIESTA" increase the capacity and quality of the tempeh brownies products.